SYSTEMS AND METHODS OF MONITORING AND TRAINING DOGS AND DETERMINING THE DISTANCE BETWEEN A DOG AND A PERSON - Mettler, Cory; Stewart, Frank M; Kania, Bruce G; Kania, Anne (2021)
Exemplary embodiments of a system for monitoring a dog comprise a control unit including a transmitter configured to transmit periodic signals and a collar unit including a receiver configured to receive the periodic signals from the transmitter. The periodic signals comprise individual signals having different power levels such that the individual signals travel different distances depending on their respective power levels. The different power levels may comprise a high-power level, a medium-power level, a low-power level, and a minimum power level. The system determines a distance between the collar unit and the control unit by determining which of the individual signals is received by the collar unit. Systems and methods of training dogs and monitoring the distance between a dog and a person also are provided.